Trends in the Development of the Land Freight Transport in Bulgaria - Dimitrov, Georgi (Research Papers, 2021)
The inland freight transport provides necessary goods and raw materials for manufacturing plants and the transportation of the finished products to the end users. It is an important factor for the rhythmic and timely supply to the commercial network with goods for the fulfilment of the everyday needs of the population for transport. The inland freight transport has a key role for the economic and social development of the country as it is a necessary condition for a normal functioning of all economic branches.The functioning of the transport system is based mainly on the fact that any mode of transport has specific features which determine the sphere of its effective usage. Under the conditions of a market economy, the self-regulation of the transport system is largely carried out which arises in the clash between the striving transport companies (carriers) for the most effective organizing of their transport activities and the requirements from customers (shippers) for quality and cheap transport services.In the current scientific study, the role of freight road and rail transport in the national transport system is consistently reviewed and analysed, as well as the quantities of goods transported by them and the performed freight transport work in the conditions of EU membership. The duration of the period under review (2007 – 2018) provides an opportunity to follow the main trends in the development of the inland freight transport in Bulgaria and based on that to develop guidelines and recommendations for its future sustainable development.
Keywords: Road freight transport; Rail freight transport; Transport work; Transport development perspectives